Archeological Tourist Destination Image Formation: Influence of Information Sources on the Cognitive, Affective and Unique Image - Huete-Alcocer, Nuria; Martinez-Ruiz, Maria Pilar; López-Ruiz, Víctor Raúl; Izquiedo-Yusta, Alicia (Frontiers in Psychology, 2019)
Image has been considered an influential factor in tourists’ perceptions and evaluations of a destination. This paper analyzes the formation of the tourist destination image of Segóbriga Archaeological Park, a cultural destination of great heritage value, located in the province of Cuenca (Spain). The image is analyzed using a multidimensional approach, considering not only its cognitive and affective components, but also the unique-image component. The latter has received less attention in the literature and is a novelty in the context of this type of cultural destination. The results show that this component is essential to the overall image of an archaeological destination and that it is not influenced by information sources. PLS-SEM was used.